2015
DOI: 10.1111/vox.12246
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of cytomegalovirus‐specific hyperimmune globulins vs. standard intravenous immunoglobulins

Abstract: Background and Objectives To evaluate standard intravenous immunoglobulin (IVIG) as an alternative to intravenous cytomegalovirus hyperimmune immunoglobulin (CMVIG) for prophylaxis and therapy of cytomegalovirus (CMV) disease, we measured the ELISA and neutralizing titres of CMV-specific antibodies in CMVIG and IVIG preparations. Results Cytomegalovirus hyperimmune immunoglobulins contained more than fourfold higher CMV ELISA and CMV-neutralizing activity per gram of IgG than the standard IVIGs. Pooled data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…In vitro studies show consistently enhanced functional antibody against CMV compared to regular intravenous immune globulin. 245,246 Monoclonal antibodies are in development and show potential promise for reduction of CMV DNAemia and disease. 247,248…”
Section: Immune Globulinmentioning
confidence: 99%
“…In vitro studies show consistently enhanced functional antibody against CMV compared to regular intravenous immune globulin. 245,246 Monoclonal antibodies are in development and show potential promise for reduction of CMV DNAemia and disease. 247,248…”
Section: Immune Globulinmentioning
confidence: 99%
“…As a result, the effect of CMVIg for the treatment of GR‐CMV is almost always confounded by the concomitant use of antiviral agents. There are no published clinical studies demonstrating the superiority of CMVIg over IVIG, and in vitro evidence is conflicting . In vitro studies use neutralizing titer to determine anti‐CMV activity, and measurements of IgG subclasses, specifically IgG3, as a surrogate marker of neutralizing titer .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…24 In a recent industry-funded study, CMVIg demonstrated 4-fold higher neutralizing activity than pooled IVIG, and there was no correlation between IgG3 and neutralizing titer between products. 24 The authors concluded that CMVIg was not less active, as was suggested in a previous study, and IgG3 levels alone do not provide assurance of high anti-CMV titers or neutralizing activity. Overall measurement of anti viral antibody activity found in IVIG products is not standardized and is highly variable.…”
Section: Immune Globulin: Cmvig and Ivigmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the remaining candidates, no simple cell culture system is available for EBV, and different neutralization assay formats exist for CMV, with unclear correlation of results with clinical relevance. 25,27,28 HAdV, RSV, and hPIV were thus finally selected for further investigation.…”
Section: Choice Of Alternative Virus Antibody Specificitiesmentioning
confidence: 99%